Simplify

4t^2- 16/8/t - 2/6

### 2 Answers | Add Yours

4t^2- 16/8/t - 2/6

16/8/t = 16/8t

We'll divide by 8 both numerator and denominator:

16/8t = 2/t

Now, we'll reduce by 2 the term 2/6:

2/6 = 1/3

The simplified given expression is: 4t^2 - 2/t - 1/3

We have to simplify: 4t^2- 16/8/t - 2/6

4t^2- 16/8/t - 2/6

=> 4t^2- (16/8)/t - (2/6)

16/8 = 2 and 2/6 = 1/3

=> 4t^2- 2/t - 1/3

**We can simplify 4t^2- 16/8/t - 2/6 as 4t^2- 2/t - 1/3.**

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes